2014
DOI: 10.1186/bf03351797
|View full text |Cite
|
Sign up to set email alerts
|

Photometric and polarimetric observations and model simulations of (216) Kleopatra

Abstract: We performed photometric and polarimetric observations, on November 8 and 9, 1999, of an M-type main belt asteroid, (216) Kleopatra by using the HBS spectropolarimeter installed at Dodaira observatory, National Astronomical Observatory of Japan (NAOJ). Photometric amplitude of lightcurve in the V band was 0.12 mag, and the averaged degree of polarization was −1.01±0.1%. It seems that the polarimetric data might also show a slight change in the degree of polarization (∼0.2%) at the second minimum of the photome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…With an equivalent radius of 62.5 km, the overall extension of the dumb-bell solution is 283 km x 89 km x 81 km, with a central waist of 38 km, which is in rough agreement with the results of Tanga et al (2001). Takahashi et al (2004b) focused on the question of Kleopatra's shape through the Roche approximation formalism. They obtained a Roche solution with a mass ration of 0.84 and a weighting parameter of 05-0.6 ( Table 2).…”
Section: Fig 8: To Be Insertedsupporting
confidence: 82%
“…With an equivalent radius of 62.5 km, the overall extension of the dumb-bell solution is 283 km x 89 km x 81 km, with a central waist of 38 km, which is in rough agreement with the results of Tanga et al (2001). Takahashi et al (2004b) focused on the question of Kleopatra's shape through the Roche approximation formalism. They obtained a Roche solution with a mass ration of 0.84 and a weighting parameter of 05-0.6 ( Table 2).…”
Section: Fig 8: To Be Insertedsupporting
confidence: 82%
“…Hestroffer et al (2002a) suggested that (216) Kleopatra most likely is very elongated, as suggested before; however, the authors could not determine whether the asteroid did consist of two components separated by a small gap, or whether it was indeed one elongated object. Takahashi et al (2004), from lightcurve simulations, tend to favor the bilobed model of Tanga et al (2001). These works presented serious caveats and evidence showing that the dog-bone shape model needs to be somehow revised and improved or at the very least compared with new imaging data with even higher spatial resolution.…”
Section: Introductionmentioning
confidence: 89%
“…A notable example is (4) Vesta (Dollfus et al 1989), which showed a 0.1% polarimetric variation, and the maximum of the polarization coincides with the lightcurve minimum, suggesting that albedo variation exists on the surface per the controlled polarization degree and visible magnitude. Similarly, (3) Juno, (9) Metis, and (216) Kleopatra showed rotational variations of 0.15-0.27 %, ∼0.1 %, and ∼0.2 %, respectively (Takahashi et al 2009;Nakayama et al 2000;Takahashi et al 2004). Although the measurement accuracy is too limited to detect such a small variations in the polarization degree, we suggest that Icarus has a quite homogeneous albedo in contrast with these asteroids because our measurement was made at a large phase angle, while these previous detections were made at a small phase angle where the polarization degree itself has small values (1/6∼1/10 of Icarus's |P r |, i.e., 0.5 |P r | 1.0%).…”
Section: Rotational Variation In P Rmentioning
confidence: 98%